2009
DOI: 10.1063/1.3262624
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 0-3 type manganite/insulator composites and manipulation of their magnetotransport properties

Abstract: In order to promote the technological applications of perovskite manganites, a great fundamental interest has been devoted to tailoring and/or enhancing their magnetotransport properties. Design and fabrication of manganite-based nanocomposites offer great potential to tailor the magnetotransport properties. In this work, we illustrate the promising concept of 0-3 type manganite/insulator composites (where manganite nanoparticles are uniformly and discretely embedded in a three-dimensional-connectivity insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…In this report, we introduce a polyacrylamide gel route to synthesize Bi 2 Fe 4 O 9 nanoparticles. Our recent work has demonstrated that the polyacrylamide gel method allows the production of high-quality nanoparticles with a uniform spherical shape [26][27][28], and also this method exhibits an excellent capability to create core-shell composite nanoparticles [26]. The photocatalytic activity of Bi 2 Fe 4 O 9 nanoparticles fabricated in the present study has been examined by the photodegradation of methyl red 0925-8388/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 95%
“…In this report, we introduce a polyacrylamide gel route to synthesize Bi 2 Fe 4 O 9 nanoparticles. Our recent work has demonstrated that the polyacrylamide gel method allows the production of high-quality nanoparticles with a uniform spherical shape [26][27][28], and also this method exhibits an excellent capability to create core-shell composite nanoparticles [26]. The photocatalytic activity of Bi 2 Fe 4 O 9 nanoparticles fabricated in the present study has been examined by the photodegradation of methyl red 0925-8388/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 95%
“…Many groups have attempted to synthesize CMR-insulator composites, such as La 0.67 Ca 0.33 MnO 3 (LCMO)-MgO [11], LCMO-BaTiO 3 (BTO) [12,13], LCMO-Al 2 O 3 [14,15], La 0.67 Sr 0.33 MnO 3 -La 2 O 3 -La(OH) 3 [16], La 0.67 Sr 0.33 MnO 3 -polyaniline [17] and LCMO-SrTiO 3 (STO) [18], etc. Incorporation of insulating materials as a second phase is believed to be advantageous to enhance extrinsic CMR behaviour as they make the GBs insulating, thus creating a barrier in the way of the charge carriers followed by an enhancement of tunneling probability.…”
Section: Introductionmentioning
confidence: 99%
“…For a better understanding of CMR a large number of studies have been carried out in single crystals [6], thin films [7,8], polycrystalline CMR materials [9,10] and CMR-based composites [11][12][13][14][15][16][17][18]. Many groups have attempted to synthesize CMR-insulator composites, such as La 0.67 Ca 0.33 MnO 3 (LCMO)-MgO [11], LCMO-BaTiO 3 (BTO) [12,13], LCMO-Al 2 O 3 [14,15], La 0.67 Sr 0.33 MnO 3 -La 2 O 3 -La(OH) 3 [16], La 0.67 Sr 0.33 MnO 3 -polyaniline [17] and LCMO-SrTiO 3 (STO) [18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…A big interest is being paid to multiferroic materials with coupled electric and magnetic properties because they can exhibit both electrical polarization induced by a magnetic field and magnetization induced by an electric field [5][6][7][8][9]. If these materials are to be used in practical applications, it is necessary to make a composite of magnetic and electric compounds with an improved magnetoelectric effect.…”
Section: Introductionmentioning
confidence: 99%